2020
DOI: 10.1088/1755-1315/425/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of green and roasted coffee bean of Gayo arabica civet coffee (kopi luwak)

Abstract: Kopi luwak, is an Indonesian exotic coffee, is known as one of most popular coffee in the world. This coffee is prepared from the finest and ripest coffee berries that are eaten by Asian civet (Paradoxurus hermaphroditus), cat like-animal. The aim of this study was to determine the chemical attributes of kopi luwak both in green and roasted coffee bean. This study conducted by collecting the six samples of kopi luwak from different farms in Gayo Highland, which then processed onto green and roasted coffee bean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
3
7
0
1
Order By: Relevance
“…Kopi Luwak coffee samples had an average caffeine content of 0.48 g/100 g (dwb) (Table 3), which is similar to that reported 2017) (0.36 g/100 g) for Kopi Luwak and that found for Jacu coffees in the present study (0.34 g/100 g, on average), but lower than that reported by Muzaifa et al (2020) (on average 1.20 g/100 g) for Kopi Luwak and that of non-bioprocessed green C. arabica samples (0.6-1.8 g/100 g) (Cheng et al, 2016). This result reinforces the previously mentioned hypothesis that bioprocessing reduces green coffee caffeine content.…”
Section: Crop Year Rather Than Location or Post-harvest Processing Di...supporting
confidence: 89%
See 2 more Smart Citations
“…Kopi Luwak coffee samples had an average caffeine content of 0.48 g/100 g (dwb) (Table 3), which is similar to that reported 2017) (0.36 g/100 g) for Kopi Luwak and that found for Jacu coffees in the present study (0.34 g/100 g, on average), but lower than that reported by Muzaifa et al (2020) (on average 1.20 g/100 g) for Kopi Luwak and that of non-bioprocessed green C. arabica samples (0.6-1.8 g/100 g) (Cheng et al, 2016). This result reinforces the previously mentioned hypothesis that bioprocessing reduces green coffee caffeine content.…”
Section: Crop Year Rather Than Location or Post-harvest Processing Di...supporting
confidence: 89%
“…The average contents of proteins (12.8 g/100 g dwb), lipids (11.5 g/100 g dwb), ashes (4.7 g/100 g dwb) and total carbohydrates (70.7 g/100 g dwb) in Kopi Luwak coffee samples (Table 2) were similar to those previously reported in the literature (Marcone, 2004;Muzaifa and Hasni, 2016;Hadipernata and Nugraha, 2018;Muzaifa et al, 2020), with the exception of the lipid contents reported by Muzaifa and Hasni (2016) (on average 1.3 g/100 g), which was much lower than expected for green coffee beans. This study is the first to report the dietary fiber contents in Kopi Luwak coffee samples (on average 56.8 g/100 g dwb) (Table 2), which were slightly higher than the 40-50% content expected to be found in green coffee beans (Trugo, 1985), possibly due to the relative decrease of digestible nutrients.…”
Section: Crop Year Rather Than Location or Post-harvest Processing Di...supporting
confidence: 88%
See 1 more Smart Citation
“…For the ash content, the highest value was obtained in Java Preanger, followed by Andung Sari and Malang. The concentration of lipid ranged from 13.15% (Andung Sari) to 13.17% (Malang) which is higher than in Gayo civet green bean coffee [8] and the trigonelline concentration was from 0.96% (Java Preanger) to 0.99% (Malang). Furthermore, percentage of Java preanger, Malang and Andung Sari coffee concentration is in the range of green coffee arabica concentration [1].…”
Section: Resultsmentioning
confidence: 75%
“…The carbohydrate concentration is lower than that of Gayo coffee around 60% [7]. Moreover, the highest concentration of CGA was obtained in Andung Sari coffee (9.1%) followed by Malang and Java Preanger coffee, this value is higher than the CGA concentration in Gayo arabica civet green bean coffee of 3.73 ± 0.61 [8]. The highest concentration of caffeine was also obtained in Andung Sari which is higher than the concentration in Gayo and Mandheling coffee from Sumatera island [9].…”
Section: Resultsmentioning
confidence: 99%